Prognostic Accuracy of the Modified CHA2DS2-VASc Score in COVID-19 Patients Admitted to the Emergency Department Due to Clinical Worsening - Valente Silva, Beatriz (2022)
Introduction: Risk factors comprising the CHA2DS2VASc score are recognized as risk factors for venous thromboembolism and mortality in COVID-19 patients. A modified CHA2DS2VASc score (M-CHA2D2VASc), developed by changing gender criteria from female to male, has been proposed to predict in-hospital mortality in COVID-19 patients. The aim of this study was to evaluate the prognostic accuracy of M-CHA2D2VASc for adverse clinical outcomes and short-term mortality in COVID-19 patients admitted to the Emergency Department.Material and Methods: Retrospective study of patients admitted to the ED who underwent computed tomography pulmonary angiography due to suspected pulmonary embolism or clinical worsening. Patients were stratified into three M-CHA2DS2-VASc risk-categories: low (0 - 1 points), intermediate (2 - 3 points) and high-risk (≥ 4 points).Results: We included 300 patients (median age 71 years, 59% male). The overall mortality was 27%. The M-CHA2DS2-VASc score was higher in non-survivors compared to survivors [4 (IQR:3 - 5) vs 2 (IQR: 1 - 4), respectively, p < 0.001). The M-CHA2DS2-VASc score was identified as an independent predictor of mortality in a multivariable logistic regression model (OR 1.406, p = 0.007). The Kaplan-Meier survival curves showed that the M-CHA2DS2-VASc score was associated with short-term mortality (log-rank test < 0.001), regardless of hospitalization (log-rank test p < 0.001 and p = 0.007, respectively). The survival proportion was 92%, 80% and 63% in the lower, intermediate, and higher risk-groups. As for the risk-categories, no difference was found in pulmonary embolism, Intensive Care Unit admission, and invasive mechanical ventilation.Discussion: This is the first study to validate M-CHA2DS2-VASc score as a predictor of short-term mortality in patients admitted to the Emergency Department.Conclusion: The M-CHA2DS2-VASC score might be useful for prompt risk-stratification in COVID-19 patients during admission to the Emergency Department.